Process of Student Adaptation of Culture Shock - Roy Schepman Mundeza (Journal La Sociale, 2021)
Cultural differences may result in culture shock for those engaged in intercultural contact. The student is one example of a student who has encountered culture shock as a result of his or her decision to study in Makassar. The purpose of this research is to ascertain the method by which students adjust to culture shock and the difficulties faced throughout the process